Meningkatkan Keaktifan Belajar Siswa Sekolah Dasar dengan Menggunakan Model Pembelajaran Cooperative Script - Dian Nurvita Anggraeni (Konsorsium Lembaga Penelitian dan Pengabdian kepada Masyarakat Perguruan Tinggi Muhammadiyah 'Aisyiyah (PTMA) Koordinator Wilayah Jawa Tengah - DIY, 2021)
The problem of second grade students at SD Negeri 2 Soropadan is the lack of studentlearning activity. The purpose of this study was to increase student activity using thecooperative script learning model. The research method used is Classroom Action Researchwhich is divided into two cycles, each cycle consisting of four stages of activity, namely thestages of planning, action, observation, and subject reflection with research as many as tenclass II SD Negeri 2 Soropadan, Pringsurat, Temanggung. . In cycle one, the data obtainedby the average score of students as a whole is 76 (76%) which has exceeded the KKM, whichis 74 with six students who have completed and four students have not completed. In cycletwo there was an increase in the average total score of 7.5 to 83.5 (83.5%) with ninestudents who completed and one student who did not finish. So, it can be said that thecooperative learning model can increase student activity in participating in the learningprocess in class II SDN 2 Soropadan, Pringsurat, Temanggung.